A Study on Performance and Reusability of Certified and Uncertified Face Masks - Haebum Lee; Seojeong Kim; HungSoo Joo; Hee-joo Cho; Kihong Park (Aerosol and Air Quality Research)
Abstract In this study, the performance (particle removal efficiency and breathing resistance) of several commercially available face masks (KF80-certified electrostatic and nanofiber filter masks, and an uncertified mask) was evaluated, along with their filter structure and composition. Also, the effects of the relative humidity (RH) of incoming air, of water and alcohol exposure, and of reuse, on the performance of face masks were examined. Monodisperse and polydisperse sodium chloride particles were used as test aerosols. Except for the uncertified mask filter, PM2.5 removal efficiency was > 90%. The nanofiber filter mask had the highest quality factor due to its low pressure drop and high removal efficiency, and densely packed nanofiber pore structure, and significant amounts of fluorine, carbon and oxygen. The removal efficiency of the KF80-certified mask was barely affected by the higher RH of incoming air. When the mask filters were soaked in water, their removal efficiency decreased. The uncertified mask filter showed the largest decrease in removal efficiency (26%). When the mask was soaked in alcohol, the removal efficiency decreased to a greater degree than when soaked in water. The nanofiber mask filter showed the strongest resistance to alcohol among the tested mask filters. During evaluation of mask reusability, the removal efficiency of certified mask filters decreased by 4% over 5 consecutive days (2 hours per day), and that for the uncertified mask filter decreased significantly, by 30% after 5 days.